Eye Movements During RAN as an Operationalization of the RAN-Reading “Microcosm” - Peters, Jessica Lee; Bavin, Edith Laura; Crewther, Sheila Gillard (Frontiers in Human Neuroscience, 2020)
Rapid Automatized Naming (RAN) is a strong predictor of reading aloud, though there is little agreement on what underpins RAN or how it relates to reading. Some theorize phonological skills, while others suggest that RAN reflects the ‘microcosm’ of cognitive and attentional processes also required for reading, with more recent research using eye movements in an attempt to study this relationship. In the current study we aimed to extend on previous investigations to identify whether the temporal patterns of eye movements predict RAN and can therefore be established as a method to study the cognitive processes underlying RAN that could then be utilized to elucidate the relationship of RAN to reading. A Gazepoint eye tracker was used to record the eye movements of 93 learner readers aged 5-8 years (M age = 7.00) while performing a custom computerized alphabetic RAN task. Text reading accuracy, comprehension and rate; nonverbal intelligence; and phonological awareness abilities were also assessed. Regression analyses showed that, independently of phonological awareness, eye movements (fixation count and fixation duration) measured during RAN tasks were highly reflective of children’s rapid naming performance (92.8%). Both mean fixation count and mean fixation duration during RAN tasks also predicted text reading accuracy (36.3%), comprehension (31.6%), and rate (36.2%) scores, and in predicting these text reading skills there was a high level of shared variance with RAN performance. In a sub-sample of participants, longer average fixation durations and counts independently discriminated children with reading difficulties (n = 18; aged 7-9) from neurotypical children matched for age (n = 18), but not from younger neurotypical children matched for reading level (n = 18; aged 5-6). Together, these results suggest that the analysis of eye movements recorded during RAN allows for the operationalization of many of the spatially and temporally-bound cognitive and attentional processes that underpin the RAN, and a step towards elucidating its relationship to reading.